Analysis of the Perceptions of Students of the Faculty of Economics and Islamic Business towards the Accountability of the Jember Amil Zakat Institution in the Digital Era - Amalia, Mildatul Anzu; Siswanto, Adil (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to analyze the perception of FEBI UIN KHAS Jember students towards the accountability of Lembaga Amil Zakat (LAZ) in Jember in the digital era. Accountability is an important aspect in zakat governance, especially in ensuring transparency of financial statements and distribution of zakat funds. Method: This research uses descriptive qualitative method with data collection techniques through interviews, observation, and documentation of FEBI students. Practical Applications: The results show that the digital era provides easy access to information about LAZ through social media and websites, so students tend to trust LAZ that actively presents information transparently. Conclusion: FEBI UIN KHAS Jember students consider LAZ accountability very important, especially in terms of transparency of financial statements and distribution of zakat funds. The presence of digital media has a significant influence on students' perceptions, where LAZs that are active in digital publications are more trusted.